The Effect of Normative Feedback on Throwing Aiming Task Learning in Adolescent with Down syndrome - Maryam Naghibzadeh; Mehdi Roozbahani; Jabar Rashnavadinejad; bijan goodarzi (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2024)
Aim and Background: Today, in all human societies, special attention is given to exceptional children, especially mentally retarded children. Serious attention to Down syndrome children due to growth failure implies significant investments by governments, especially in the field of rehabilitation. Therefore, it is necessary to consider appropriate exercises, encouragement and feedback for the development of motor skills of these children. Therefore, the aim of this study was to investigate the influence of normative feedback on Learning in adolescent with Down syndrome. Methods and Materials: Thirty boy adolescent syndrome are participated as volunteer and they are classified in three groups of control, positive and negative normative feedback randomly. The necessary information for this research was collected in 4 stages of pre-test, acquisition test, retention and transfer. The acquisition phase consisted of 7 blocks of 10 trials. In this phase, all groups received real feedback after each trial and positive and negative normative feedback groups received normative feedback about their performance after each block of 7 trials. One day after the practice phase retention and transfer test without feedback was performed to assess learning. One-Way ANOVA with Repeated Measures, ANOVA and Tukey tests were used to data analysis (P≤0.05). Findings: Positive normative feedback improved their accuracy and consistency score across practice trials, retention and transfer test, but other groups didn't improve their accuracy and consistency score. There were significant difference between control and negative normative feedback groups with positive normative feedback but there were no significant difference between control and negative normative feedback groups. Conclusions: The findings highlight the importance of motivational influences on motor learning in adolescent with Down syndrome and was concluded that motor learning of such children could be improved using cheer, in such a way that punishment is eliminated